Meta-Analisis Simulasi Virtual dalam Pembelajaran untuk Mendukung Berpikir Kritis - Ismail Ismail (Bioscientist : Jurnal Ilmiah Biologi, 2021)
This study aims to conduct an analysis based on available data sources (meta-analysis) on the trend of using virtual simulations in learning to support critical thinking. The SCOPUS database was used as the data source in this study. This meta-analysis study was conducted in December 2021 by including the keywords “virtual, simulation, learning, and critical thinking” in the search documents section on the SCOPUS page. In the initial search, 112 documents were found, this includes all “subject areas, documents, and source types” and in the range from 1999 to 2021. Not a single document was found under 1999. The subject areas included are social sciences, computer science, and others (a total of 23 subject areas). Contains 8 documents and source types (articles, conference papers, book chapters, and others). The results are documented in (.csv) and (.ris) files. The files are processed using Microsoft Excel for document graphic visualization by year, print screens of SCOPUS data sources for document types and subject areas, and comprehensive analysis of quantitative data displayed on SCOPUS data sources. Finally, the results in this study show that the research trend of virtual simulation in learning to support critical thinking has penetrated in many fields. The assessment of SCOPUS primary data sources shows journal articles as the most “document and source type” (50%) followed by conference papers and others. In addition, social science is the most document “subject area” (28.2%) followed by computer science and others.